Shedding Light on Student Learning Through the Use of Lightboard Videos - Peter Rogers; Diana Botnaru (International Journal for the Scholarship of Teaching and Learning, 2019)
This mixed-method study examined the effect of Lightboard videos on student learning and perceptions in a Flipped Classroom Model (FCM). The study targeted 68 civil engineering undergraduate students at a 4-year public university in Southeastern USA. Lightboard videos were intentionally alternated between two consecutive semesters. Within the same section of the course, classes without Lightboard videos served as a control group and classes with Lightboard videos served as a study group. Both sections were taught by the same instructor utilizing the same materials and assessments for the class. Student academic performance was measured using in-class assignments. Additional quantitative and qualitative data were collected through an end-of-semester survey. Data show a modest academic performance increase on the overall score on in-class assignments and an improvement of average student scores on 69.2% of the in-class assignments in the study group. The overall means on the Likert scale survey showed a strong endorsement of Lightboard videos for understanding, engagement and satisfaction. Students commented positively on the collaborative aspect of in-class problem solving in FCM.